Cuboctahedron-based indium–organic frameworks for gas sorption and selective cation exchange. Issue 51 (2nd June 2016) - Yu, Panpan; Li, Qipeng; Hu, Yue; Liu, Nannan; Zhang, Lijie; Su, Kongzhao; Qian, Jinjie; Huang, Shaoming; Hong, Maochun
Abstract : InOF-9 is an anionic indium–organic framework, which exhibits excellent gas sorption capacity through supercritical carbon dioxide activation process and selectively encapsulates guest methylene blue cations. Abstract : [Me2 NH2 ]3 [In3 (BTB)4 ]·2DMF·2DMA·28H2 O (InOF-9 ) is an anionic indium–organic framework based on nanosized cuboctahedrons, which is sustained by tetrahedral [In(COO)4 ] nodes and 3-connected tricarboxylates. AlthoughInOF-9 is structurally unstable when exposed to air, it exhibits excellent gas sorption capacity through a supercritical carbon dioxide activation process and selectively encapsulates guest methylene blue cations.